Development of HOTS-Based Student Worksheets on Force and Motion Materials to Improve Students’ Critical Thinking Skills - Indah Permata Sari Pasaribu; Nirwana Anas (Sakura Digital Nusantara, 2026)
Critical thinking is an essential higher-order thinking skill in 21st-century learning because it enables students to analyze information, evaluate problems, draw conclusions, and construct logical arguments. However, preliminary observations showed that fourth-grade students still experienced difficulties in developing critical thinking skills in science learning, particularly on the topic of Force and Motion. Therefore, this study aimed to develop a Higher Order Thinking Skills (HOTS)-based Student Worksheet (LKPD) that is valid, practical, and potentially useful for supporting students’ critical thinking skills. This study employed a Research and Development (R&D) approach using the 4D development model, consisting of Define, Design, Develop, and Disseminate stages. The limited classroom trial involved 20 fourth-grade students at SD Pelangi. Data were collected through pretests and posttests, material and media expert validation sheets, observations, interviews, and teacher and student response questionnaires. The data were analyzed using validity analysis, practicality analysis, and N-Gain analysis to identify learning improvement. The results showed that the HOTS-based LKPD met highly valid and practical criteria. Material expert validation reached 98%, while media expert validation reached 93%, both categorized as “very valid.” The teacher practicality score reached 84%, categorized as “very practical,” and student responses showed highly positive results. The classroom trial also indicated an improvement in students’ learning outcomes, with the average pretest score increasing from 39.5 to 88.5 in the posttest. The N-Gain score reached 0.80, which is categorized as high. These findings suggest that contextual HOTS-based activities can support students’ participation and critical thinking processes in science learning. The developed LKPD can be used as an alternative learning material to support student-centered science instruction. However, further studies involving larger samples and control groups are needed to examine its effectiveness more rigorously.